Unveiling Cultural Insights in Pramoedya Ananta Toer’s ‘Rumah Kaca': A Sociopragmatic Analysis - Yunita Warinangin; Rosmawati (Winaya Inspirasi Nusantara Foundation, 2025)
Background of the problem: Literature not only reflects human beauty and creativity but is also a forum for conveying deep messages about life, philosophy and culture. Purpose: This research aims to analyze the expression of cultural values in the story construction of the novel